Al-Islām al-Thawrī: Mushkilat al-Ḥājj Mohammad Misbāch - Zahrah, Siti (Studia Islamika, 1997)
H. Mohammad Misbach was born in 1876 in Kauman, Surakarta, from batik successful merchant family. As an adult he could wrestle batik trading business, to be successful. Because her character is revolutionary and happy association, Misbach finally abandon their batik and began to cultivate the intellectual. Misbach entry of a West Irian Jaya (Inlandsche Journalisten Bond) in 1914 and the merger with Sarekat Islam (SI) marked the beginning of his involvement in the world of movement. Moving his religious outlook of Islam, suggests that Misbach want to "move Islam" as the power to transform colonial socio-political order, not just to legitimize and maintain it.DOI: 10.15408/sdi.v4i1.789